Preparing Tomorrow’s Teachers Using the Teacher Educator Technology Competencies (TETCs) - Nicole Luongo (The Advocate, 2019)
This article examines the preparation of tomorrow’s teachers by analyzing higher education teacher educators' attitudes towards the Teacher Educator Technology Competencies (TETCs). The study was based on the national education requirements that have been established by the U.S. Department of Education’s Office of Educational Technology, International Society for Technology in Education (ISTE) and the Council for Accreditation of Educator Preparation (CAEP). The study focused on the current assumption that all teacher candidates will leave teacher preparation programs ready and able to use technology effectively in PK-12 classrooms. The researcher administered an online survey to a sample of teacher educators in order to identify their attitudes towards the TETCs. The main questions in this study included: (1) What are the attitudes of teacher educators towards the TETCs?, and (2) What are the professional development needs for teacher educators? The researcher offers various suggestions for future professional development options for teacher educators and teacher preparation programs. Some of these options include developing and administering educational technology workshops, moving away from stand-alone educational technology courses, and integrating technology into all teacher preparation courses.
Keywords: International Society for Technology in Education (ISTE); National Education Technology Plan (NETP); teacher candidates; teacher educators; Teacher Educator Technology Competencies (TETCs); Technological Pedagogical and Content Knowledge (TPACK)